Interlanguage Analysis on Indonesian EFL Learnersâ€™ Compositions - Maheswari, Putu Ayu Masita; Adnyani, Ni Luh Putu Sri; Suwastini, Ni Komang Arie (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2020)
This study aims at investigating the interlanguage production by Indonesian EFL students in their English compositions. Interlanguage describes the language produced by second or foreign language learners when learning the target language. Forty college students majoring in English for tourism industry were the subjects in this study. In collecting the data, the students were asked to write a recount text with a topic "an experience of visiting a hotelâ€ through a guided writing exercise. The framework of error analysis and interlanguage analysis were used in analyzing the data. The result shows that the studentsâ€™ interlanguage production is influenced by both Indonesian language as their native language (NL) and English as the target language (TL). The influences were found in both lexical and grammatical forms. This study implies that in learning a foreign language, errors are made by students and by knowing the errors, teachers and tutors can apply appropriate strategies and materials to enhance learning.